2012
DOI: 10.1002/jlcr.2961
|View full text |Cite
|
Sign up to set email alerts
|

Imaging agents for myeloperoxidase

Abstract: The myeloperoxidase (MPO) inhibitors 1 and 2 were prepared as their isotopologues with carbon-14, carbon-13, and nitrogen-15 or tritium with high specific activity and purity. Starting from potassium [ 14 C]cyanide or [ 14 C]formate provided metabolically stable 14 C-labels on [ 14 C]-1 and [ 14 C]-2. Catalytic hydrogenation was used for the preparation of [ 3 H]-2, giving multiple enriched positions as shown by 3 H NMR. 1 and 2 are promising in vitro and in vivo imaging radioligands and have the potential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Treatment of 3 with tritium gas and palladium on carbon afforded 4 and subsequent hydrolysis with sodium hydroxide in methanol afforded the deprotected benzaldehyde 5 . Finally, a tetrachlorosilane catalyzed multicomponent one‐step fusion of 5 with the indene 6 and thiourea gave 1 with a specific activity of 0.90 TBq/mmol and a 99% radiochemical purity after purification. Four months later, a resynthesis was needed as the substance had decomposed completely upon storage at −20°C.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of 3 with tritium gas and palladium on carbon afforded 4 and subsequent hydrolysis with sodium hydroxide in methanol afforded the deprotected benzaldehyde 5 . Finally, a tetrachlorosilane catalyzed multicomponent one‐step fusion of 5 with the indene 6 and thiourea gave 1 with a specific activity of 0.90 TBq/mmol and a 99% radiochemical purity after purification. Four months later, a resynthesis was needed as the substance had decomposed completely upon storage at −20°C.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that a 3 H-radioligand from this pyrrolo-pyrimidone series could specifically label inflammatory lesions in the spinal cord known to express MPO in a murine model of autoimmune encephalomyelitis [9]. In addition, it has been demonstrated that increase in brain MPO expression in animal models can be imaged using MRI and bis-5HT-DTPA(Gd) [19,20].…”
Section: Pet Measurementsmentioning
confidence: 98%
“…AZD3241 and related pyrrolo-pyrimidone compounds have previously been labeled with carbon-14 in the thio-carbonyl position in a 4-step reaction starting from [ 14 C]potassium cyanide [9,15]. The previously demonstrated rapid transformation of [ 14 C]potassium cyanide to benzoyl [ 14 C]isothiocyanate via [ 14 C]potassium thiocyanate and the scope for optimizing reaction times in subsequent steps (Malmquist, personal communication) suggested that a similar route could have a potential also for 11 C-radiolabeling.…”
Section: Radiochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium 14 C-formate was prepared in situ after a reduction of [ 14 C]­CO 2 with superhydride LiEt 3 BH. After the solution was concentrated, the precursor 3 was added in the presence of EDCI to form the corresponding formylated intermediate, which was further converted into the desired product 4 under basic conditions . The overall radiochemical yield from CO 2 was low (8%), but sufficient compound was delivered to be administered to rats for quantitative whole body autoradiography (QWBA) experiments.…”
Section: Radiocarbon Labelingmentioning
confidence: 99%